Analisis Faktor-Faktor Yang Mempengaruhi Pilihan Karir Mahasiswa Farmasi Di Sekolah Tinggi Ilmu Farmasi Riau - Yulia Indri Yani (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2019)
Employment contract or prospects in the field of pharmacy are very variable, but the pharmacy staff are not evenly distributed. This is probably due to the factors that influence the career choice of a pharmacy worker. The aim of this study was to determine the main factor influencing the choice of career and student career choice direction and see the impact of demographic data on factors influencing students' career choices. This type of research is a descriptive analytical study conducted using a survey. The sampling technique used is a stratified random sample. The respondents in this study were 120 students, consisting of student class of 2014, 2015, 2016 and 2017 at the School of Pharmacy Riau. From the survey, the vast majority of pharmacy students opted for a career in hospital (RS) 34.2%, in one after another with 27.5% pharmaceutical industry, University / Research Institute 26.7%, pharmaceutical wholesalers (PBF) 5.8% and pharmacy 5.8%. Based on the results of univariate data analysis, there are three very important factors that influence the career choices of students salary / income, (the benefits) and work environment. From the results of the unpaired t-test between male students and female there are three factors that have a significant difference, is a factor of salary / income, working hours flexible and geography, while in beginning students with the final level there is no significant difference of each factor factors that influence the choices of the student career.